Chitosan-alginate nanoparticles as effective oral carriers to improve the stability, bioavailability, and cytotoxicity of curcumin diethyl disuccinate. (15th March 2021) - Sorasitthiyanukarn, Feuangthit Niyamissara; Muangnoi, Chawanphat; Rojsitthisak, Pornchai; Rojsitthisak, Pranee
Graphical abstract: Highlights: Encapsulation of CDD in CANPs enhanced its stability during simulated digestion. CDD-CANPs exhibit a higher chemical stability during UV-light exposure. Encapsulation of CDD in CANPs increased its bioaccessibility during simulated digestion. Encapsulation of CDD in CANPs increased its bioavailability five-fold. CDD-CANPs had a higher cellular uptake and anticancer activity in HepG2 cells than free CDD. Abstract: Curcumin diethyl disuccinate (CDD) is an ester prodrug of curcumin that has better chemical stability in phosphate buffer (pH 7.4) and anticancer activities against MDA-MB-231 human breast cancer cells and Caco-2 cells than curcumin. However, a major drawback of CDD is its poor water solubility and low bioavailability in the gastrointestinal tract. To overcome these problems, a nanoformulation was developed using chitosan/alginate nanoparticles (CANPs) under the optimal condition as previously derived by statistical optimization. The CDD-loaded CANPs (CDD-CANPs) were found to exhibit good stability after exposure to simulated digestive fluids and ultraviolet light, and a sustained-release profile of CDD in the simulated digestive and body fluids. The in vitro release pattern fitted well to the Peppas-Sahlin model, indicating that the release of CDD was mainly governed by diffusion. Compared to free CDD, the CDD-CANPs showed better stability, bioaccessibility, bioavailability, cellular uptake, and cytotoxicity against HepG2 cells.